A Fully CNN Based Fingerprint Recognition System - Abrishambaf, Reza; Demirel, Hasan; Kale, Izzet (IEEE, 2008)
In this paper, a fully Cellular Neural Networks (CNN) based fingerprint recognition system is introduced. The system includes a preprocessing phase where the input fingerprint image is enhanced and a recognition phase where the enhanced fingerprint image is matched with the fingerprints in the database. Both preprocessing and recognition phases are realized by means of CNN approaches. A novel application of skeletonization method is used to perform ridgeline thinning which improves the quality of the extracted lines for further processing, and hence increases the overall system performance.
11th International Workshop on Cellular Neural Networks and Their Applications -- JUL 14-16, 2008 -- Univ Santiago de Compostela, Santiago de Compostela, SPAIN